Determination of the Appropriate Vehicle Operating in Particular Urban Traffic Conditions - Ondrej Stopka; Branislav Sarkan; Maria Chovancova; Larisa M. Kapustina (Communications - Scientific letters of the University of Zilina, 2017)
This paper presents selection of the most appropriate vehicle intended to operate on a particular urban territory, using the specific methods of multi-criteria analysis. For selecting the suitable vehicle, it is necessary to determine a number of specific criteria. In the paper, the desired vehicle is selected from five vehicles, while, each of them has a different product brand. To determine the weights of criteria, the Saaty pairwise comparison method is applied, and subsequently, the multi-criteria evaluation of alternatives is utilized for a research problem.